Investigating the Dependency between Electricity and the Human Development Based on Metaheuristic Optimization - Molu, Reagan Jean Jacques; Mbasso, Wulfran Fendzi; Naoussi, Serge Raoul Dzonde; Kenfack, Saatong Tsobze; Wira, Patrice (International Journal of Energy Economics and Policy, 2022)
Having access to electricity is one of the big challenges nowadays. It is a basic requirement for any community as it can improve the living standards characterized via the improvement of healthcare, education, and the local economy at large. Henceforth, electricity plays a major role in the economic and social development in many countries. The United Nations are working to ensure an easy access to safe energy technologies as from 2030. To cope with this point of view, this paper aims to use the relation between electricity and the Human Development Index (HDI) in order to predict the value of HDI in a short term. In this relation, two parameters x and y are used to study the dependency between the HDI and electricity consumption and production conjointly. To fulfill our goal, the values of electricity production, electricity consumption and HDI for a period are used into our optimization technique namely Particle Swarm Optimization (PSO). The best values of our parameters x and y are obtained under different scenarios based on three criteria: number of iterations, population, and limit of convergence. The results obtained after simulations leads to the value of HDI of about 0.68 in 2030, with 100 iterations, 100 populations and 0.05 as limit of convergence. The predicted value obtained is closed of the theoretical value presented into the Electricity Sector Development Plan. Thus, this helps to appreciate the impact of energy on the social and economic development of Cameroon.